(untitled) (Psychology Travelogs, 2025)
This article explores resilience as a critical psychological resource for military personnel operating under wartime conditions. Resilience is conceptualized as the capacity to adapt effectively to stress and recover from traumatic experiences. The research provides a detailed characterization of different types of resilience: physical, psychological, emotional, and social. These dimensions are examined in the context of their role in mitigating the negative effects of combat stressors, physical exertion, and psycho-emotional challenges on the mental health of military personnel. The study highlights the results of diagnostics conducted using the CD-RISC-10 resilience scale, which measures overall resilience levels, and the «Personal Resources» methodology (developed by O. Savchenko and S. Sukach), which assesses individual psychological strengths. These diagnostic tools reveal significant variations in the resilience levels among military personnel, influenced by their exposure to combat situations, emotional stability, and social support systems. The article also emphasizes the psychological impact of sustained exposure to high-stress environments, including the risks of burnout, anxiety, and post-traumatic stress. To address these challenges, the authors propose targeted interventions to support the mental health and adaptive capacities of service members. Specific recommendations include the development and implementation of psychological support programs. These programs are vital for fostering long-term recovery and ensuring operational effectiveness during and after combat. The findings underline the importance of resilience as a multidimensional resource that not only safeguards the mental health of military personnel but also enhances their capacity to perform effectively in extreme conditions.